Mindfulness-Based Intervention Does Not Influence Cardiac Autonomic Control or the Pattern of Physical Activity in Fibromyalgia During Daily Life: An Ambulatory, Multimeasure Randomized Controlled Trial. Issue 5 (May 2017) - Grossman, Paul; Deuring, Gunnar; Walach, Harald; Schwarzer, Barbara; Schmidt, Stefan
Abstract : Objectives: Fibromyalgia (FM) is a syndrome characterized by severe pain, fatigue and sleep disturbance. There is evidence of central hyper-responsiveness to sensory stimulation and impaired cardiovascular autonomic control. Laboratory investigations suggest that mindfulness-based stress reduction (MBSR) may improve autonomic functioning in FM. However, these findings may not reflect what occurs during naturalistic conditions, and MBSR studies during real-life functioning are lacking. We conducted a randomized controlled, 3-armed study with 168 female FM patients. This report describes cardiac, respiratory, and physical activity findings. Methods: Eight-week MBSR was compared with wait-list and active control intervention. Ambulatory accelerometry and cardiorespiratory function were monitored over 24-h periods at 3 time points: preintervention, postintervention, and at the 8-week follow-up. Also, baseline levels were compared with an age-matched group of 33 healthy women. Findings: Activity heart rate, respiratory sinus arrhythmia, and ventilation were measured. Comparison with controls confirmed differences in cardiac autonomic tone and activity pattern among patients. Most measures also showed effects of time of day and point of measurement. Regarding the intervention study, there were no effects of treatment. In addition, there were no relations between patient-reported clinical improvement and objective physiological or accelerometry parameters. Intervention-related benefits in wellbeing were not associated with changes in daytime cardiorespiratory measures or pattern of physical activity. Conclusions: MBSR did not produce cardiac autonomic benefits or changes in daily activity in FM. Furthermore, the lack of an association between patient-experienced clinical improvement and objective physiological measures suggests that subjective changes in the wellbeing of FM patients over time are not related to alterations in the cardiorespiratory autonomic function or activity levels.